Indonesia's View: Eradicating Colonialism and Supporting Palestine - Fajriyah, Nurul; Setiawati, Siti Muti'ah (Institute of International Studies, 2025)
This research aims to analyze the reasons behind Indonesia's continued support for Palestine despite facing challenges both domestically and internationally. The approach used involves the concepts of interest and continuity. From a national interest perspective, Indonesia aims to demonstrate religious and humanitarian solidarity. From an international interest perspective, Indonesia seeks to assert itself as a global leader in human rights, strengthen its camaraderie with developing countries, and fulfill its role as a member of international organizations, such as the UN Security Council and the Organization of Islamic Cooperation (OIC), in maintaining world peace. Furthermore, Indonesia's support for Palestine has been notably consistent from its early independence until the Jokowi administration. Using an explanatory method and data collection through library research, this study concludes that although Indonesia's support for Palestine has not succeeded in ending the conflict with Israel, these efforts have showcased Indonesia's courage in challenging the status quo and bolstering its diplomatic position and identity in international politics.